2012
DOI: 10.1007/s00359-012-0747-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of learning and memory of Apis cerana and Apis mellifera

Abstract: The honeybee is an excellent model organism for research on learning and memory among invertebrates. Learning and memory in honeybees has intrigued neuroscientists and entomologists in the last few decades, but attention has focused almost solely on the Western honeybee, Apis mellifera. In contrast, there have been few studies on learning and memory in the Eastern honeybee, Apis cerana. Here we report comparative behavioral data of color and grating learning and memory for A. cerana and A. mellifera in China, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
1
29
0
1
Order By: Relevance
“…Foragers of Ac may make more foraging trips per day than foragers of Am (no data yet). Ac is known to perform significantly better in learning on both color and grating patterns than Am [23], so perhaps they can locate sparse nectar resources more easily. Another difference may be metabolic rates.…”
Section: Discussionmentioning
confidence: 99%
“…Foragers of Ac may make more foraging trips per day than foragers of Am (no data yet). Ac is known to perform significantly better in learning on both color and grating patterns than Am [23], so perhaps they can locate sparse nectar resources more easily. Another difference may be metabolic rates.…”
Section: Discussionmentioning
confidence: 99%
“…When the choice frequencies of honeybees for the “positive” pattern remained stable at above 80%, the training was ended. As this study continues our previous behavioral studies of learning and memory in honeybees, details of the maze experiments can be found in our previous paper (Qin et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Compared with A. mellifera, A. cerana has actually been shown to learn better in a controlled laboratory setting (Chen 2001;Qin et al 2012). Wang and Tan (2014) showed that A. cerana is as amenable as A. mellifera to the study of olfactory learning using the PER assay.…”
Section: Introductionmentioning
confidence: 97%